ANTIOXIDANT ACTIVITY OF POMEGRANATE - O., Lazeeza S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Natural fruits antioxidants play a significant role in inhibiting reactive oxygen species and scavenging free radicals, thus avoiding chronic, degenerative diseases such as cardiovascular disease, aging, cholesterol rates and cancer. The study covered six categories of each three tastes of different pomegranate fruits obtained or purchased in Erbil/Kurdistan-Iraq, a total of 54 samples (6x3x3) were analyzed. Each type was tested for ferric reduction of antioxidant power assay, reduced power method, ascorbic acid content, total phenol and total flavonoid. Our results have shown that the Sour Smilan cultivar has the highest antioxidant properties, ferric antioxidant power reduction (536.89±14.65), ferric power reduction (0.965), ascorbic acid content (0.252±0.012), total phenol (139.66±3.49), total flavonoid (23.08±2.23), and short comparative studies have been conducted to analyze the amount of iron (11) in pomegranate in order to analyze their interferences to the antioxidant activity reported in the ferric reduction of antioxidant power assay.